Optimizing the role of al-Qur’an educational parks to improve children's achievements and character formation during the Covid-19 pandemic - Subur Subur; Dwi Marvia Ningsih; Sriyatun Sriyaun; Navida Kurniatanti; Septiana Regilta Rahayu; Listiana Listiana (Universitas Muhammadiyah Magelang, 2022)
In all aspects of life, including education, the Covid-19 pandemic has shifted from offline to online. Because of the limitations of internet facilities and their supporters, as well as human resources who are not ready for online learning, parents in Kacetan Village find online learning to be extremely burdensome. As a result of TPQ Nurul Iman's role, parents hope for an online learning workshop to help their children with their schoolwork. This activity aims to provide school learning assistance so that TPQ students can grasp learning material and realize their potential in academic and non-academic fields. The Contextual Teaching and Learning (CTL) method was chosen because it allows the teacher to encourage students to connect what they've learned and put it into practice in their daily lives. The implementation of this activity includes educational film showings, online learning workshops, social parenting, dowry preparation, infrastructure repair, student outbound, and soft skills development.